Brain insulin resistance in down syndrome: involvement of PI3K-AKT/MTOR axis in early-onset of Alzheimer's disease and its potential as a therapeutic target - Azimzadeh, Mansour; Cheah, Pike-See; Ling, King-Hwa (Elsevier, 2024)
Down syndrome (DS) is the most common genetic cause of intellectual impairment, characterised by an extra copy of chromosome 21. After the age of 40, DS individuals are highly susceptible to accelerated ageing and the development of early-onset Alzheimer-like neuropathology. In the context of DS, the brain presents a spectrum of neuropathological mechanisms and metabolic anomalies. These include heightened desensitisation of brain insulin and insulin-like growth factor-1 (IGF-1) reactions, compromised mitochondrial functionality, escalated oxidative stress, reduced autophagy, and the accumulation of amyloid beta and tau phosphorylation. These multifaceted factors intertwine to shape the intricate landscape of DS-related brain pathology. Altered brain insulin signaling is linked to Alzheimer's disease (AD). This disruption may stem from anomalies in the extracellular aspect (insulin receptor) or the intracellular facet, involving the inhibition of insulin receptor substrate 1 (IRS1). Both domains contribute to the intricate mechanism underlying this dysregulation. The PI3K-Akt/mammalian target of the rapamycin (mTOR) axis is a crucial intracellular element of the insulin signaling pathway that connects numerous physiological processes in the cell cycle. In age-related neurodegenerative disorders like AD, aberrant modulation of the PI3K-Akt signaling cascade is a key factor contributing to their onset. Aberrant and sustained hyperactivation of the PI3K/Akt-mTOR axis in the DS brain is implicated in early symptoms of AD development. Targeting the PI3K-Akt/mTOR pathway may help delay the onset of early-onset AD in individuals with DS, offering a potential way to slow disease progression and enhance their quality of life.